TECHNICAL EFFICIENCY OF SOYBEAN PRODUCTION IN NIGER STATE, NIGERIA - Mairabo, A.; Jibrin, S.; Audu, H.; Salihu, M. Y.; Elisha, Y. (FUDMA Journal of Sciences, 2023)
The efficiency with which farmers use resources and technologies available to them are imperative in boosting production. However, activities of armed bandits, conflict between farmers and pastoralists, rising prices amid decreasing consumer purchasing power and diminishing household incomes are some factors that impede agricultural production. Therefore, the objective of this study was to determine the technical efficiency of soybean production among small holder farmers in Niger State. A three stage sampling technique was used to select 150 respondents for the study. Primary data collected with the aid of structured questionnaires were analyzed using stochastic frontier Cobb-Douglas production function model. Results showed that the mean technical efficiency level of the respondents was 0.89 which implies that a typical soybean farmer in the study area could increase output by 11% using the same input bundle. Also, the efficiency model shows that coefficients of farm size, seed quantity and labour were positively significant which indicates that that increase in these variables will lead to increase in technical efficiency. The inefficiency model reveals that coefficients of credit and extension visit were positively significant while those of age and farming experience were negatively significant. This means that as credit and extension visit increases, technical efficiency decreases; while increase in age and farming experience will increase technical efficiency. The study recommended that extension services should be streamlined so that farmers do not receive conflicting information as this could hinder efficiency in production. Also, credit given to farmers should be monitored to ensure effective utilization.